Między historią a filozofią. Poetyka powieści Wiktora Pielewina „Mały palec Buddy” - Chudzińska-Parkosadze, Anna (Studia Rossica Posnaniensia, 2016)
The article focuses on the concept of a dualistic model of the world perception in the novel Chapayev and Void by Victor Pelevin. The model represents the contrast to the notion of alchemic union that stands for the ideal pattern, which cannot be realized in Russian reality. So dualism meant as a division and separation between heroes, who cannot understand each other, concerns also the division between East and West in the historical, philosophical and cultural perspective. However, the main division, which is superior upon the others, is the dualism of reality and consciousness that in the novel transforms to the universal category. The only possible escape from this dysfunctional realm is spiritual illumination.